Caprine hamburger enriched with different albumin concentrations: Physical and physical-chemical aspects (Research, Society and Development, 2021)
Northeast Brazil has been showing prominence when it comes to goat farming, being the main economic activity of many families. However, this branch still needs improvement when it comes to technologies used in the products offered, associating this to the population's need for nutritionally more elaborate and easily accessible foods is that the present research is justified. The present study had the general objective of obtaining and characterizing goat meat hamburgers increased with different concentrations of albumin. The study was of an experimental and exploratory character carried out at the Technological Vocational Center - CVT - Campus Pombal - PB. Goat meat was purchased in the city of Piancó - PB, thus valuing the local production, after the removal of the inedible parts, six formulations were elaborated, varying between the standard and with 2%, 4%, 6%, 8% and 10% supplementation of albumin in relation to goat meat. After the preparation of the samples, they were characterized by means of physical and physical-chemical analyzes. The results presented show that all formulations were within the recommendations of the resolutions for hamburgers, with emphasis on the increase in the protein level of the final product. It can be seen from the present study that it is possible to improve goat burgers from albumin supplementation without negatively affecting the final product, improving its nutritional aspects.